2018
DOI: 10.1539/joh.2018-0020-oa
|View full text |Cite
|
Sign up to set email alerts
|

Management of occupational noise induced hearing loss in the mining sector in South Africa: Where are the audiologists?

Abstract: Objective: This study was conducted to explore the scope of practice for occupational audiologists in the mining industry and the audiologists' involvement in hearing conservation programmes in South African mines. Additionally, this study investigated the mining industry's role in the audiologists' involvement, and assessed the audiologists' levels of preparedness for working in occupational audiology. Methods: In-depth, qualitative telephone and face-to face interviews were conducted with seven occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Primary care physicians should aim to enquire about patient's noise exposure and to refer patients for elementary hearing conservation services (audiometry, counselling, and personal hearing protective devices) [25]. Moreover, audiologists and otolaryngologists see patients who have significant unprotected occupational and non-occupational noise exposure, and as such they play an important role in providing counselling, hearing protection and periodic audiometry for these patients [26]. Finally, clinical interventions such as the use of magnesium or antioxidants such as N-acetylecysteine for preventing noise-induced hearing loss may also hold some promise in the treatment of age-related hearing loss [7,27].…”
Section: Plos Onementioning
confidence: 99%
“…Primary care physicians should aim to enquire about patient's noise exposure and to refer patients for elementary hearing conservation services (audiometry, counselling, and personal hearing protective devices) [25]. Moreover, audiologists and otolaryngologists see patients who have significant unprotected occupational and non-occupational noise exposure, and as such they play an important role in providing counselling, hearing protection and periodic audiometry for these patients [26]. Finally, clinical interventions such as the use of magnesium or antioxidants such as N-acetylecysteine for preventing noise-induced hearing loss may also hold some promise in the treatment of age-related hearing loss [7,27].…”
Section: Plos Onementioning
confidence: 99%
“…It is therefore possible that our study population is still exposed to occupational noise, even with legislated hearing conservation programmes. One possible contributor to the lack of progress towards the elimination of occupational NIHL may be the fact that occupational audiologists are only marginally involved in the development and implementation of hearing conservation programmes (Moroe & Khoza-Shangase, 2018). Kanji et al (2018) recommend that the occupational audiologists in South African mines should play an important role in individualised education during audiological testing in order to enhance the effectiveness of hearing conservation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Audiologists are responsible for educating and training mineworkers on the negative impact of ONIHL. However, in South Africa, evidence indicates that there are a few audiologists employed in the mining sector as mines prefer services of audiometrists who are considered more cost effective [30]. Edwards [6] commented that mines have a lack of qualified professionals, who possess knowledge and skills on how to teach adults to achieve health promotion and behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a study conducted on the management of ONIHL in the mining sector revealed awareness training of mineworkers as one of the successes realized by the mining sector [7].…”
Section: Introductionmentioning
confidence: 99%